Pediatric central nervous system infections in the Amazon: clinical and laboratory profiles - Marinho, Eveny Perlize Melo; Ferreira, Ewerton da Silva; Barrionuevo, Caio Cesar Leiva Bastos; Melo, Sabrina Araújo; Cordeiro, Jady Shayenne Mota; Pinto, Sergio Damasceno; Monte, Rossicleia Lins; da Silva, Valderjane Aprígio; Martins, Yasmin Ferreira; Reis, Monique Freire; Tufic-Garutti, Samantha dos Santos; Sampaio, Vanderson de Souza; et al. (Frontiers in Public Health, 2023)
Background Central nervous system (CNS) infections are important causes of mortality and morbidity in children, and they are related to severe problems such as hearing loss, neurological sequelae, and death. The objective was to describe clinical and laboratory exam profiles of children who were diagnosed with CNS infections. Methods We conducted a cross-sectional study based on medical records, which included pediatric patients aged from 3 months to 15 years, with a clinical suspicion of CNS infection between January 2014 to December 2019. The pathogens were confirmed in cerebrospinal fluid (CSF) samples using Gram staining, cell culture, molecular diagnostics (PCR and qPCR), and serology. Results Out of the 689 enrolled patients, 108 (15.6%) had laboratory-confirmed infections in CSF. The most common bacterial pathogens isolated from the culture were Neisseria meningitidis serogroup C in 19, Streptococcus pneumoniae in 11, and Haemophilus influenzae in seven samples. The viruses identified were Enterovirus, Cytomegalovirus, Varicella-zoster virus, Epstein–Barr virus, and arbovirus. No patient was found to be positive for Herpes simplex virus 1 and 2. Patients with viral infections showed altered levels of consciousness (p = 0.001) when compared to bacterial infections. Conclusion This study shows the presence of important vaccine-preventable pathogens, and different families of viruses causing CNS infections in the pediatric patients of Manaus.